Preparation method of semi-raspberry-shaped Janus particles, method for modifying semi-raspberry-shaped Janus particles with chiral carbon dots and application of semi-raspberry-shaped Janus particles
By preparing semi-raspberry Janus particles modified with chiral carbon dots, the problem of difficulty in detecting enantiomers of chiral compounds in the prior art is solved, and the efficient recognition effect in fluorescence detection is achieved.
Patent Information
- Application Number
- CN202411214454.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to detect enantiomers of chiral compounds quickly and accurately, and the commonly used methods are complex and costly.
Semi-raspberry-like Janus particles were prepared by using polystyrene as seeds, glycidyl methacrylate and ethylene glycol dimethacrylate as monomers and crosslinking agents, and by hydrothermal method Chiral carbon dots were prepared, Janus particles were modified for fluorescence detection.
It realizes rapid and accurate identification of chiral substances, especially in fluorescence detection, which has significant fluorescence quenching of L-lysine, providing a simple, fast and low-cost detection method.
Smart Images

Figure CN119431674A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer preparation, and relates to a method for preparing a polymer by polymer cross-linking, and also relates to a carbon dot-modified preparation method and an application thereof in fluorescence detection, and specifically relates to a method for preparing semi-raspberry-shaped Janus particles, the preparation of chiral carbon dot-modified semi-raspberry-shaped Janus particles, and an application thereof in fluorescence detection. Background Art
[0002] In nature, chirality is considered to be an important property widely present in organisms, from small molecules of amino acids to large molecules of proteins, DNA and RNA. Molecules or compounds with chirality usually exist in left-handed or right-handed forms, called enantiomers. Although the enantiomers of these chiral substances have the same elements and functional groups, their chemical properties are sometimes very different. Thalidomide is one of them. One of its enantiomers has a therapeutic effect on the complications of leprosy, while the other enantiomer can cause fetal malformations. The methods commonly used to distinguish the enantiomers of chiral compounds include nuclear magnetic resonance, liquid-mass spectrometry, chromatography and circular dichroism. However, the above methods require expensive instruments and more professional personnel and are complicated to operate. Therefore, there is an urgent need for a simple, fast and accurate method to detect chiral isomers. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a half-raspberry-shaped Janus particle with low cost and capable of quickly identifying chiral substances, a method for preparing a half-raspberry-shaped Janus particle modified with carbon dots, and an application thereof in fluorescence detection.
[0004] In order to achieve the above object, the present invention first provides a method for preparing half-raspberry-shaped Janus particles, comprising:
[0005] Using polystyrene as seeds, glycidyl methacrylate (GMA) as monomer, and ethylene glycol dimethacrylate (EDMA) as cross-linker, semi-raspberry-shaped Janus particles with morphological and chemical anisotropy were prepared by photoinduced seed swelling method.
[0006] In the above method, the preparation of semi-raspberry-shaped Janus particles: the polystyrene seeds with uniform particle size are prepared by dispersion polymerization. First, 0.9g PVP, 0.1-10g AIBN, 10mL styrene and 45mL ethanol are added to a round-bottom flask; the solid is completely dissolved by ultrasound, and then mechanically stirred at room temperature for 15min, the speed is 1-150r / min, and the temperature is raised to 30-70℃ for reaction for 1-8h; the obtained product is separated by centrifugation, washed three times with ethanol, and then dispersed in 0.2-1% SDS solution for storage;
[0007] Then, 1-9 mL of an aqueous solution consisting of PVA (1-5%) and SDS (0.2-1%) is added to a 50 mL volumetric tube. The organic phase consisting of a monomer (GMA), a crosslinker (EDMA) and an organic porogen is mixed with the PVA-SDS solution. The photoinitiator DMPA is dissolved in the organic phase. Under the action of ultrasound, the organic phase is mixed with the aqueous phase to form an oil-in-water emulsion;
[0008] Finally, the polystyrene seeds were oscillated in an oscillating shaker at a speed of 1-200 r / min for 1-20 hours to swell in the presence of an organic phase, and irradiated with 365 nm ultraviolet light for 1-2 hours. The product was centrifuged, washed three times with water and ethanol respectively, and then freeze-dried in a vacuum to obtain semi-raspberry-shaped Janus particles.
[0009] In the above method, the average particle size of the polystyrene seeds is 1.79 μm.
[0010] The average particle size of the semi-raspberry-shaped Janus particles obtained by the above method is 3.4 μm.
[0011] In the above preparation process, the organic porogen is at least one of n-propanol, n-pentanol, cyclohexanol, benzyl alcohol, n-decanol and dodecanol. Preferably, the porogen is dodecanol and cyclohexanol.
[0012] In the above steps, preferably, the amount of AIBN added is 0.1 g, the rotation speed is 150 r / min, the heating temperature is 60° C., and the reaction time is 6 h. In addition, the organic porogen can be selected from toluene, p-xylene, mesitylene, dodecanol, n-decanol, p-xylene, cyclohexanol and n-propanol, and dodecanol and cyclohexanol are preferred in the present invention.
[0013] The present invention also provides a method for preparing chiral carbon dot-modified semi-raspberry-shaped Janus particles. The semi-raspberry-shaped Janus particles obtained by the above method are used to prepare a chiral carbon dot by a hydrothermal method with citric acid and S-1,1'-bi-2-naphthylamine / R-1,1'-bi-2-naphthylamine as precursors, and the chiral carbon dot is grafted onto the semi-raspberry-shaped Janus particles to obtain chiral carbon dot-modified semi-raspberry-shaped Janus particles.
[0014] The above methods can be divided into:
[0015] Preparation of chiral carbon dots: 1-100 mg of citric acid and 1-200 mg of S-1,1'-bi-2-naphthylamine were dispersed in 80 mL of pure water, transferred to a 50 mL polytetrafluoroethylene reactor after ultrasonic stirring, and heated at 0-180 ° C for 1-8 h. After the reactor was naturally cooled, the obtained mixture was filtered with a 0.22 μm filter membrane and dialyzed for 24 h using a cellulose dialysis membrane (Da: 3000) to obtain chiral carbon dots S-CD. According to the above operation process, R-CD was prepared using citric acid and R-1,1'-bi-2-naphthylamine as raw materials.
[0016] Functionalization of the chiral carbon dots on the surface of the semi-raspberry-shaped Janus particles, and grafting the chiral carbon dots onto the semi-raspberry-shaped Janus particles: first, 1-10 mL of S-CD solution is dispersed in 110 mL of water, 50 mg of semi-raspberry-shaped particles are added thereto, ultrasonicated for 10 min to make them evenly dispersed, heated and stirred at 60° C. for 6 h, and finally the obtained product is centrifuged at 6000 r / min and washed with ultrapure water until no fluorescence is generated when the supernatant is irradiated with an ultraviolet lamp, and the obtained washed product is the chiral carbon dot-modified semi-raspberry-shaped Janus particle PS-CD.
[0017] The chiral carbon dots were grafted onto only one side of the semi-raspberry-shaped Janus particles, and the fluorescence detection limit for L-lysine was 8.69 nmol / L.
[0018] The present invention provides chiral carbon dots obtained based on the preparation method of the carbon dot-modified half-raspberry-shaped Janus particles, and also provides an application of carbon dot-modified half-raspberry-shaped Janus particles in fluorescence detection, which has a significant fluorescence quenching phenomenon for L-lysine in aqueous solution.
[0019] Specifically, in the fluorescence experiment, a suspension with a concentration of 0.01-0.5 mg / L was prepared by dispersing a certain amount of PS-CD in water, and L-lysine standard solutions of different concentrations (0-800 nmol / L) were prepared. The L-lysine solutions (9 mL) of different concentrations were mixed with the PS-CD suspension (1 mL), and their fluorescence intensity was measured by fluorescence spectrophotometry.
[0020] Preferably, the concentration of the PS-CD suspension added in the above fluorescence experiment is 0.2 mg / L.
[0021] The technical effects of this application are:
[0022] In the invention, polystyrene was used as a seed, glycidyl methacrylate (GMA) as a monomer, and ethylene glycol dimethacrylate (EDMA) as a crosslinker to prepare semi-raspberry-shaped Janus particles with morphological and chemical anisotropy through a photoinduced seed swelling method. A chiral carbon dot was also prepared by a hydrothermal method using citric acid and S-1,1'-bi-2-naphthylamine / R-1,1'-bi-2-naphthylamine as precursors, and grafted onto the semi-raspberry-shaped Janus particles, and finally fluorescence detection of L-lysine was achieved using fluorescence spectrophotometry.
[0023] This application benefits from the development of nanotechnology. Nanoparticles and their derivatives have excellent optical activity, good stability and adjustable emission wavelength, and are ideal materials for detecting chiral isomers. In recent years, carbon dots (CDs) have received widespread attention as an emerging luminescent carbon nanomaterial, especially its excellent luminescent properties, and its preparation method is more environmentally friendly and safer than traditional quantum dots. The preparation of CDs is usually environmentally friendly, its precursors are widely available and very rich, and the production cost is low. However, when it exists alone, it is prone to agglomeration, which makes it unstable. This application combines it with Janus particles with chemical anisotropy to retain its original properties while greatly improving its stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Particles (a) P-1, (b) P-2, (c) P-3, (d) P-4, (e) P-5, (f) P-6, (g) P-7, (h) P-8, and (i) P-9 prepared using a single porogen.
[0025] Figure 2 These are the SEM images of microspheres prepared using dodecanol / cyclohexanol as porogens (a) P-10, (b) P-11, (c) P-12, and (d) P-13.
[0026] Figure 3 (a, b) TEM images of CD, (c) particle size distribution of CD and (d) circular dichroism spectra of R-CD and S-CD.
[0027] Figure 4 (ac) Fluorescence imaging of PS-CD.
[0028] Figure 5 (a) Fluorescence emission spectra of S-CD with 7 amino acids and (b) fluorescence intensity at 425 nm, (c) fluorescence emission spectra of PS-CD with different concentrations of L-Lys and (d) linear response curve for detecting L-Lys, (e) fluorescence emission spectra of P@N-CD with different concentrations of L-Lys and (f) linear response curve for detecting L-Lys. DETAILED DESCRIPTION
[0029] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0031] Preparation of experimental drugs: DMA, GMA, diethyl benzoate (DMPA), styrene, citric acid, R-1,1'-bi-2-naphthylamine and S-1,1'-bi-2-naphthylamine were purchased from Shanghai Aladdin. Polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), azobisisobutyronitrile (AIBN), sodium dodecyl sulfate (SDS), dodecanol, n-decanol, p-xylene, cyclohexanol, n-propanol and toluene were purchased from Tianjin Damao. L / D-tryptophan (L / D-Trp), L / D-Lys, L / D-alanine (L / D-Ala), L / D-tartaric acid (L / D-Tart), L / D-proline (L / D-Pro), L / D-cysteine (L / D-Cys) and L / D-aspartic acid (L / D-Asp) were purchased from Inokai Reagent Co., Ltd. The above reagents were not further purified. The water used in the experiment was deionized water.
[0032] Preparation of experimental equipment: Scanning electron microscope (SEM) images were obtained by JEM-7500F from JEOL, Japan. Transmission electron microscope (TEM) images were obtained by HT7700 microscope from JEOL, Japan. Fluorescence spectra of materials were analyzed by LS-55 fluorescence spectrometer from Shimadzu, Japan.
[0033] Example 1
[0034] Preparation method of semi-raspberry-shaped Janus particles
[0035] Preparation of Half Raspberry Janus:
[0036] First, 0.9 g PVP, 0.1 g AIBN, 10 mL styrene and 45 mL ethanol were added to a round-bottom flask; the solid was completely dissolved by ultrasound, and then mechanically stirred at room temperature for 15 min, the speed was 150 r / min, and the temperature was raised to 60°C for reaction for 6 h; the obtained product was separated by centrifugation, washed three times with ethanol, and then dispersed in 0.5% SDS solution for storage;
[0037] Then, 9 mL of an aqueous solution consisting of PVA (mass concentration 2%) and SDS (mass concentration 0.5%) was added to a 50 mL volumetric tube, and an organic phase consisting of a monomer (GMA), a crosslinking agent (EDMA) and an organic porogen was mixed with the PVA-SDS solution. The photoinitiator DMPA was dissolved in the organic phase. Under the action of ultrasound, the organic phase and the aqueous phase were mixed to form an oil-in-water emulsion.
[0038] Finally, the mixture was shaken at 150 r / min for 18 h in an oscillating shaker to allow the polystyrene seeds to swell in the presence of an organic phase. The mixture was irradiated with 365 nm ultraviolet light for 2 h, and the product was centrifuged, washed three times with water and ethanol, respectively, and then freeze-dried in a vacuum to obtain semi-raspberry-shaped Janus particles.
[0039] In this embodiment, polystyrene seeds were first prepared by dispersion polymerization, and then an aqueous solution of 2% PVA and 0.5% SDS was selected as the aqueous phase as an emulsion stabilizer to maintain the phase interface. The oil phase consisted of a monomer GMA, a crosslinking agent EDMA, a photoinitiator DMPA and a porogen. The aqueous phase and the oil phase were then mixed and fully emulsified with the aid of ultrasound to form an oil-in-water emulsion. By adjusting the preparation conditions, such as the porogen system, etc., phase separation occurred under the irradiation of ultraviolet light, and Janus particles with different morphologies and chemical anisotropy were prepared.
[0040] In order to investigate the effect of the porogen system on the morphology of Janus particles, the seed amount was first fixed at 90 mg, the molar ratio of monomer to crosslinker was 2 / 1, and the effect of the porogen system on the morphology of Janus particles was investigated. The types of porogens used can be divided into polar porogen systems and non-polar porogen systems according to their polarity. The polar porogen system is composed of n-propanol, n-pentanol, cyclohexanol, benzyl alcohol, n-decanol and dodecanol.
[0041] like Figure 1 As shown in Figures ac, when n-propanol, n-pentanol and cyclohexanol were used as single porogens, P-1, P-2 and P-3 did not show Janus morphology. When n-pentanol was used as a porogen, the P-2 particles were almost not formed, and a certain degree of cross-linking occurred, the spheres were cracked, and the dispersion was poor. As far as we know, the solubility of GMA and styrene in n-pentanol is not high, which limits their phase separation under ultraviolet light irradiation, which may be the reason for the rupture of P-2 particles. The yields of the particles prepared under this condition were 23.6%, 11.7% and 48.2%, respectively, and the average particle size was 2.2-2.5μm.
[0042] When the porogen system is benzyl alcohol, n-decanol or dodecanol, P-4, P-5 and P-6 show obvious morphological changes.
[0043] When benzyl alcohol was used as the porogen, the P-4 particles formed flower-like microspheres ( Figure 1 d), with an average particle size of 3.1 μm and a yield of 67.2%. When n-decanol is used as a porogen, P-5 is still spherical ( Figure 1 e), but a clear dividing line appeared on its surface, dividing the surface of the microsphere into two interfaces, one half is rough and the other half is smooth, with a particle size of 2.3 μm and a yield of 38.5%. When dodecanol was used as a porogen, a rugby-shaped particle P-6 ( Figure 1 f), the average particle size was 2.2 μm and the yield was 38.7%.
[0044] In a single non-polar porogen system, toluene, p-xylene or mesitylene were selected as porogens for exploration. Figure 1 As shown in gi, when toluene is used as the porogen, the morphology of P-7 is pellet-shaped ( Figure 1 g), the particle size is about 2.6μm, and many small holes with a size of 300-800nm can be observed on its surface, with a yield of 59.5%; when p-xylene is used as a porogen, the P-8 particles are hemispherical particles ( Figure 1 h), with a particle size of 2.3 μm and a yield of 45.1%. When mesitylene was used as a porogen, P-9 did not show a special morphology, but was a spherical shape with a smooth surface ( Figure 1 i), the particle size was 2.1 μm and the yield was 38%.
[0045] like Figure 2 As shown in a, when the porogen is dodecanol / cyclohexanol with a volume of 1 / 1 (P-10), semi-raspberry-shaped Janus particles are obtained with an average particle size of 3.4 μm and a yield of 53.6%, indicating that the particles are fully swollen, have good dispersibility, and have a relatively uniform particle size. It can be found that the raspberry-shaped protrusions are only distributed on one side of the microsphere, and there are no raspberry-shaped protrusions or sticky small particles on the other side, and the boundary line on the surface of the microsphere is relatively obvious.
[0046] When the porogen is dodecanol / cyclohexanol with a volume ratio of 2 / 1 (P-11), rugby-shaped Janus particles are prepared with an average particle size of 2.1 μm and a yield of 31.7%. It can be observed that a large number of small particles adhere to the surface, and a certain degree of adhesion occurs. When the content of dodecanol is further increased, when the volume ratio of dodecanol / cyclohexanol is 3 / 1 (P-12), the morphology of the Janus particles is still rugby-like, but the particle size is uneven, and no small particles adhere to the surface, and the average particle size is 2.9 μm.
[0047] When the ratio of dodecanol is lowered, it can be found that P-13 (dodecanol / cyclohexanol volume ratio is 1 / 2) is still rugby-shaped. According to the above results, it can be found that in the mixed binary system composed of dodecanol and cyclohexanol, the morphology of Janus particles is dominated by dodecanol, and the prepared microspheres are roughly rugby-shaped. By adjusting the ratio of dodecanol and cyclohexanol, when the volume ratio is 1 / 1, semi-raspberry-shaped Janus particles can be prepared. This is because the swollen seeds, under the action of surface tension and elastic tension, make the monomers inside the seeds move to one side, and finally form semi-raspberry-shaped Janus particles under the irradiation of ultraviolet light.
[0048] Example 2
[0049] Preparation of chiral carbon dots modified semi-raspberry-shaped Janus particles:
[0050] Preparation of chiral carbon dots: 50 mg of citric acid and 145 mg of S-1,1'-bi-2-naphthylamine were dispersed in 20 mL of pure water, ultrasonically stirred for 30 min, and then transferred to a 50 mL polytetrafluoroethylene reactor and heated at 180 ° C for 8 h. After the reactor was cooled naturally, the obtained mixture was filtered with a 0.22 μm filter membrane and dialyzed with a cellulose dialysis membrane (Da: 3000) for 24 h to obtain chiral carbon dots S-CD.
[0051] The chiral carbon dots were grafted onto the semi-raspberry-shaped Janus particles: first, 2 mL of S-CD solution was dispersed in 10 mL of water, 50 mg of semi-raspberry-shaped particles were added thereto, ultrasonicated for 10 min to make them evenly dispersed, heated and stirred at 60° C. for 6 h, and finally the obtained product was centrifuged at 6000 r / min and washed with ultrapure water until no fluorescence was generated when the supernatant was irradiated with ultraviolet light. It was named PS-CD.
[0052] Then 50 mg of half-raspberry-shaped particles, 53 mg of citric acid and 34 μL of ethylenediamine were dispersed in 10 mL of water and heated at 160°C for 6 h in a polytetrafluoroethylene-lined high-pressure reactor. The obtained product was centrifuged at 6000 r / min with water, and the separated product was washed with ultrapure water until no fluorescence was generated when the supernatant was irradiated with ultraviolet light. The washed product was the chiral carbon dot-modified half-raspberry-shaped Janus particle PS-CD.
[0053] TEM images of S-CD are shown in Figure 2. Figure 3 As shown in a and b, it can be seen that the S-CD prepared by the hydrothermal method has good dispersibility and is approximately spherical in shape. The particle size distribution is analyzed by the Gaussian calculation model ( Figure 3c), it can be found that the average particle size is 3.25nm. The circular dichroism spectra of R-CD and S-CD prepared by hydrothermal method using citric acid, R-1,1'-bi-2-naphthylamine or S-1,1'-bi-2-naphthylamine as raw materials are shown in Figure 3 d. R-CD exhibits a positive Cotton effect peak and a negative Cotton effect peak at 210nm and 240nm, while the circular dichroism spectrum of S-CD exhibits a negative Cotton effect peak and a positive Cotton effect peak at 210nm and 240nm, respectively. The symmetrical circular dichroism spectra of R-CD and S-CD indicate that we have successfully prepared two CDs with opposite chirality.
[0054] Fluorescence imaging of PS-CD Figure 4 As shown in ac, carefully compare Figure 4 From the small picture in ac, we can see that under the excitation wavelength of 405nm, only the side with raspberry-shaped protrusions of PS-CD emits blue fluorescence, while the other side does not emit blue fluorescence. This is because the prepared semi-raspberry-shaped particles are composed of two phases of GMA and styrene, with epoxy groups on one side and benzene rings on the other side. Figure 4 It can be seen that the surface of S-CD has abundant amino groups, which makes S-CD react with the epoxy on the semi-raspberry-shaped particles, and S-CD is only grafted to the side with epoxy groups.
[0055] Example 3
[0056] Application of carbon dot-modified semi-raspberry-shaped Janus particles in fluorescence detection, detection of L-lysine by P@N-CD in aqueous solution: In order to verify the fluorescence selectivity of CD, the effects of several representative amino acids on the fluorescence properties of CD were measured. The fluorescence selectivity of PS-CD was tested using 7 amino acids. 7 amino acid solutions (100 μmol / L) were added to the PS-CD suspension (0.1 mg / L) to determine its fluorescence intensity.
[0057] like Figure 5As shown in a and b, it can be found that the blank sample has a higher fluorescence intensity, which is conducive to the subsequent determination of its fluorescence properties. When L-Tart is added, it can be found that the fluorescence intensity of S-CD increases slightly, while when D-Tart is added, the fluorescence intensity of S-CD hardly changes. When L-Lys is added, the fluorescence intensity of S-CD decreases significantly, and the quenching degree is as high as 85%. When D-Lys is added, the fluorescence intensity only decreases slightly, and the quenching degree is less than 25%. This is related to the spatial position between S-CD and the chiral substance, and the steric hindrance affects the interaction between them. In addition, when other amino acids are added, the fluorescence intensity changes, but the change does not exceed 10%. The above results show that S-CD shows good selectivity for L-Cys in the detection of 7 amino acids.
[0058] In order to study the fluorescence detection ability of PS-CD for L-Lys, we conducted fluorescence quenching experiments with different concentrations of L-Lys. The Stern-Volmer equation was used to quantify the fluorescence quenching degree of PS-CD:
[0059] F0 / F=1+K sv [c]
[0060] F0 and F are respectively without added MnO4 - and adding MnO4 - The fluorescence intensity after K sv is the fluorescence quenching constant, [c] is the MnO4 - concentration.
[0061] like Figure 5 As shown in c, when the excitation wavelength of PS-CD is 270 nm, the fluorescence intensity at 379 nm gradually decreases as the L-Lys concentration increases from 0 to 600 nmol / L. Figure 5 As can be seen from d, the fluorescence intensity of PS-CD is linearly correlated with the concentration of L-Lys, with a linear correlation coefficient of r = 0.9976, and the fitting equation of PS-CD is F0 / F = 0.0026[c] + 0.9411. The limit of detection (LOD) is calculated by LOD = 3σ / s, where σ is the relative standard deviation of the fluorescence intensity without L-Lys addition, and s is the slope of the calibration curve. Then, the LOD of PS-CD for L-Lys was calculated to be 8.69nmol / L.
[0062] Comparative Example 1
[0063] 50 mg of half-raspberry-shaped Janus particles, 50 mg of citric acid and 20 μL of ethylenediamine were dispersed in 80 mL of water and heated at 120°C in a polytetrafluoroethylene-lined high-pressure reactor for sufficient reaction. The obtained product was centrifuged with water until no fluorescence was generated when the supernatant was irradiated with ultraviolet light. The product was named P@N-CD.
[0064] When the excitation wavelength of P@N-CD is 370nm, the emission wavelength is 449nm, but in the range of 0-600nmol / L, the fluorescence intensity at 449nm is not linearly related to the concentration of L-Lys, and quantitative detection cannot be achieved. This is because N-CD does not have chirality and cannot selectively detect chiral substances. The change in its fluorescence intensity may be caused by the change in the pH value of the system when L-Lys is added.
[0065] It can be seen from the above results that the PS-CD prepared by the present invention can achieve quantitative detection of L-Lys in the range of 0-600nmol / L.
[0066] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing half-raspberry-shaped Janus particles, characterized in that: This method uses polystyrene as seeds, glycidyl methacrylate as a monomer, and ethylene glycol dimethacrylate as a cross-linking agent to prepare semi-raspberry-shaped Janus particles with morphological and chemical anisotropy through a photoinduced seed swelling method.
2. The method for preparing the semi-raspberry-shaped Janus particles according to claim 1, characterized in that: Specifically: 0.9 g PVP, 0.1-10 g AIBN, 10 mL styrene and 45 mL ethanol were mixed and dissolved, and the product was separated after sufficient reaction, and the product was washed with ethanol, and then the washed product was dispersed in a 0.2-1% SDS solution for storage; Then, an aqueous solution consisting of 1-5% PVA by mass and 0.2-1% SDS by mass is added into a container, an organic phase consisting of glycidyl methacrylate monomer, ethylene glycol dimethacrylate crosslinking agent and organic porogen is mixed with the PVA-SDS solution, and a photoinitiator DMPA is dissolved in the organic phase. Under the action of ultrasound, the organic phase is mixed with the aqueous phase to form an oil-in-water emulsion; Finally, the polystyrene seeds were fully vibrated in an oscillating shaker to swell in the presence of an organic phase, and were illuminated with 365 nm ultraviolet light. The product was centrifuged, washed with water and ethanol respectively, and then freeze-dried in a vacuum to obtain semi-raspberry-shaped Janus particles.
3. The method for preparing the half-raspberry-shaped Janus particles according to claim 1, characterized in that: The organic porogen is at least one of n-propanol, n-pentanol, cyclohexanol, benzyl alcohol, n-decanol and dodecanol.
4. The method for preparing the half-raspberry-shaped Janus particles according to claim 3, characterized in that: The organic porogens are dodecanol and cyclohexanol.
5. A semi-raspberry-shaped Janus particle prepared by the preparation method according to any one of claims 1 to 4.
6. A method for preparing chiral carbon dot-modified semi-raspberry-shaped Janus particles, characterized in that: Using the semi-raspberry-shaped Janus particles of claim 5, a chiral carbon dot is prepared by a hydrothermal method with citric acid and S-1,1'-bi-2-naphthylamine / R-1,1'-bi-2-naphthylamine as precursors, and the chiral carbon dot is grafted onto the semi-raspberry-shaped Janus particles to obtain chiral carbon dot-modified semi-raspberry-shaped Janus particles.
7. The method for preparing chiral carbon dot-modified semi-raspberry-shaped Janus particles according to claim 6, characterized in that: Specifically: Preparation of chiral carbon dots: 1-100 mg of citric acid and 1-200 mg of S-1,1'-bi-2-naphthylamine were dispersed in 80 mL of pure water, and after ultrasonic stirring, they were transferred to a 50 mL polytetrafluoroethylene reactor for heating reaction. After the reaction, the reactor was naturally cooled, and the obtained mixture was filtered with a filter membrane, and dialyzed with a cellulose dialysis membrane to obtain chiral carbon dots S-CD; The chiral carbon dots are grafted onto the semi-raspberry-shaped Janus particles: first, 1-10 mL of the chiral carbon dot S-CD solution is dispersed into 110 mL of water, 50 mg of the semi-raspberry-shaped Janus particles are added thereto, and ultrasonication is performed to make the dispersion uniform. After sufficient heating and stirring, the obtained product is separated, and the separated product is washed with ultrapure water until no fluorescence is generated when the supernatant is irradiated with an ultraviolet lamp. The washed product obtained is the semi-raspberry-shaped Janus particles PS-CD modified with chiral carbon dots.
8. The method for preparing chiral carbon dot-modified semi-raspberry-shaped Janus particles according to claim 7, characterized in that: The chiral carbon dots were grafted onto only one side of the semi-raspberry-shaped Janus particles.
9. A chiral carbon dot-modified semi-raspberry-shaped Janus particle prepared by the preparation method according to any one of claims 6 to 8.
10. Application of chiral carbon dot-modified semi-raspberry-shaped Janus particles in fluorescence detection.
Citation Information
Cited By
Preparation method and application of S-(-)-alpha-methylbenzylamine chiral carbon quantum dots
CN117603684A